(3GdPNjQ hGdYOI aj TQM GdoHQOIs - (3eMeO Ydj Hf YdGf GdUOjbjs
(3ChdgG (B:s
(3CeG HYO(B: (3agPG JYdjb dWja Ydi GdbUjOI GdeHfjI Yf ceGd GdehOI GdeSeGI HGdHQO GdYGQa HGddg GdHhUjQj hSejJg GdPNQ hGdYOI aj TQM GdoHQOI s
(3BNQgG (B:s
(3hcGf Pdc HeScfj HLHd CHj bHjS JbHd Gddg Pdc Hefg, hgh MSHj hfYe Gdhcjd hdG Mhd hdG bhI EdG HGddg GdYdj GdYXje s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B256 s
Keywords: (3GdCOHs